Exploring the influence of green growth and energy sources on “carbon-dioxide emissions”: implications for climate change mitigation - Akther, Sharmin; Sultanuzzaman, Md Reza; Zhang, Yanrong; Almutlaq, Fahad; Huq, Md Enamul (Frontiers in Environmental Science, 2024)
Climate change is a global concern driven by greenhouse gas emissions. Bangladesh, being densely populated and a significant carbon emitter, must urgently reduce its "carbon-dioxide emissions".The primary objectives of this research are to meticulously examine the impact of green growth, non-renewable energy, renewable energy, and technological innovations on carbon dioxide emissions in Bangladesh from 1990 to 2020, with the goal of informing policies for effective and sustainable climate change mitigation in Bangladesh. The analysis using advanced econometric methods, including autoregressive distributed lag, fully modified ordinary least squares, and canonical cointegrating regression, reveals that green growth and technological innovations have adverse long-term but positive short-term effects on carbon-emissions in Bangladesh. Additionally, it is noteworthy that both non-renewable and renewable energy sources significantly contribute to long-term and short-term carbon emissions. The study confirms the Environmental Kuznets Curve, showing a " ∩ "-shaped relationship between green development and carbon emissions.Policymakers should prioritize green growth, incentivize technological innovation, promote sustainable economic practices, and implement comprehensive energy transition strategies. The insights from this study inform policy formulation to address the complex relationships between green growth, energy sources, and carbon-dioxide emissions for sustainable climate change mitigation in Bangladesh. Bangladesh's efforts contribute to global emission reduction and foster a resilient future.